IMPLEMENTASI PIPELINE PRODUCTION ANIMATION 3D MEDIA PROMOSI UNIVERSITAS MAJALENGKA - Tri Ferga Prasetyo; Dadan Zaliluddin; Maulana Ibrahim; Amam Nur Affandi (Universitas Alma Ata, 2024)
This study focuses on the implementation of a 3D animation production pipeline in promotional media, utilizing a variety of information technology tools to optimize processes and enhance visual effectiveness. The use of Agile project management software facilitates efficient team collaboration and rapid adaptation to changes, increasing productivity and design iteration quality. In the modeling and rendering processes, Blender and Autodesk Maya are employed to create complex 3D models and detailed visuals, supported by GPU processing to accelerate rendering and allow greater creative exploration. Unity is integrated to develop interactive simulations, adding game elements to the animations that enhance user engagement. Machine learning is applied in character rigging to automate and correct poses, reducing production time and improving visual expression. Procedural generation techniques are used to automate the creation of textures and environmental elements, is applied in the final presentation phase to deliver promotional content more immersively. This research reveals the significant potential of integrating information technology in speeding up 3D animation production and enhancing the visual and interactive user experience.